Creative Strategy of CRAST FM Radio Podcast Program “Podcrast” in Maintaining the Existence of Campus Radio in the Digital Era - Qurratul'aini, Yasmina; Mulawarman, Krisna (Jogjakarta Communication Conference (JCC), 2025)
Community radio faces challenges in maintaining its existence amid shifting digital media consumption patterns. CRAST FM Radio, as a campus radio, developed the Podcrast program as a creative strategy to adapt to these changes. Initially distributed via Spotify, Podcrast later expanded to YouTube in an audio-visual format to reach a broader audience through media convergence.This research aims to analyze the creative strategies applied in the Podcrast program to maintain the existence of campus radio. Using a case study method, data were collected through in-depth interviews, observation, and documentation with informants comprising the Creative Director Coordinator, Deputy Coordinator, and Production Team of Podcrast. The findings show that Podcrast's creative strategy includes adapting content to current trends, flexible and collaborative production processes, and the use of social media (TikTok, Instagram) for promotion and audience engagement. The program segments, such as SRASI and POCI demonstrate content innovation tailored to different audience segments. Evaluation is conducted informally through reflective discussion, supporting continuous learning and improvement. In conclusion, Podcrast's creative strategy emphasizing media convergence, community building, and content innovation effectively strengthens CRAST FM's position as a digital campus media and ensures its sustainability amid the evolving digital media landscape.